"Anketiranje" v prvi polovici 19. stoletja - Visočnik, Julijana (Bogoslovni vestnik, 2023)
In 2021, all preserved topographical-historical descriptions of the parishes of the Diocese of Ljubljana were published within the framework of AES 43. In accordance with the bishop’s instructions, parish priests or chaplains of individual parishes more or less diligently, i.e., more or less extensively prepared the outlines of their parishes. At the time (if not earlier), data collecting with the help of questionnaires was already established across Europe. The efforts of the Archduke John in Styria and of Bishop Gruber in Ljubljana Diocese are especially interesting for our area, whereby they both probably derived from a similar (if not the same) context and vantage point. Work of both was in some sense upgraded by Georg Göth, who compiled his questionnaires thoughtfully but not too extensively, which helped to ensure that the responses were actually done and submitted by the addressees. The paper wants, first of all, to expose the little known and therefore rarely used material that is often of key value as it is only one that has actually been preserved. The survey questionnaires of the beginning of and middle of the 19th century therefore need to be reexamined and correctly reevaluated, if possible, establish their interdependence or influence that they had on each other, and show the latest findings on the specific case of Hoče parish.
Keywords: archduke John; bishop Gruber; first half of the 19th; Georg Göth; historical evolution of questionnaires; nadvojvoda Janez; prva polovica 19.st.; škof Gruber; topografphical-historical descriptions of parishes; topografsko-zgodovinski opisi župnij; zgodovinski razvoj anket